Investigation of air flow in selective laser melting for part production with consistent mechanical properties - Tan, Ervin Ming Ken (Nanyang Technological University, 2020)
With the rapid improvement of technology, Additive Manufacturing is created to increase productivity. It is defined as the process of making products through fusing/adding materials layer by layer, which is the direct opposite of Subtractive Manufacturing. Additive Manufacturing helps to reduce waste materials and if used correctly, reduce the cost and time used while increasing the product quality. It is based on three categories – liquid, solid or powder-based system. For this research, the main focus will be on Selective Laser Melting (SLM) which is a powder-based system. In order to maintain the mechanical properties of products made in SLM, much research had been done to figure out the factors affecting it. One of the important factors is the gas flow used in SLM chamber. Gas flow helps to remove unwanted by-products while creating an inert atmosphere to prevent any unnecessary chemical reactions with the metal powder by using an inert gas such as Argon. Gas flow needs to be effective and efficient in removing by-products. In this study, the author used ANSYS Fluent, a Computational Fluid Dynamics software to do simulations of gas flow in SLM chamber to investigate the behaviour of gas flow with different models.